Assessing the Sectoral Dynamics of Non-performing Loans: Signs from Financial and Real Economy - Bogdan MOINESCU; Adrian CODIRLAŞU (Theoretical and Applied Economics, 2012)

(untitled)
The paper is an attempt at studying the mechanisms whereby the economic activity dynamics and money market conditions affect the developments in nonperforming loan ratio across the main activity sectors, namely agriculture, industry, commerce and constructions. The default rates are modeled both on the basis of a linear approach and via a logistic function, starting from the methodological solution of the reputed conditional risk model referred to as Credit Portfolio View. The robustness of the analytical framework is ensured by applying SUR estimation method for simultaneous systems of equations in combination with that of autoregressive vectors. The empirical analysis is based on unique set of quarterly data, which allows for assessing the quality of non-financial companies loan repayment. The relevant explanatory variables were used in various configurations and lags for constructing several macroeconomic credit risk models.